Exploration of differentially expressed mRNAs and miRNAs for pediatric acute myeloid leukemia - Wang, Qing; Yue, Chao; Liu, Qin; Che, Xuchun (Frontiers in Genetics, 2022)
Abstract Background: To establish a comprehensive differential gene profile for pediatric acute myeloid leukemia patients (pAML) based on two independent databases and verify the differentially expressed genes using in vitro and in vivo analysis. Methods: The mRNA and miRNA sequencing information of GSE2191 and GSE35320, clinical recruited pAML individuals and human AML cell line (NB4 cells) were utilized in the study. Results: Compared with control sample, pAML patients demonstrated a total of 778 differentially expressed genes, including 565 up-regulated genes and 213 down-regulated genes. The genes including ZC3H15, BCLAF1, PPIG, DNTTIP2, SRSF11, KTN1, UBE3A, PRPF40A, TMED5 as well as GNL2 were top 10 potential hub genes. At the same time, 12 miRNAs demonstrated remarkable differential expressions in pAML individuals compared with control individuals, as 5 up-regulated and 7 down-regulated miRNAs. The hsa-miR-133, hsa-miR-181 as well as hsa-miR-195 were significantly down-regulated. Building a miRNA-mRNA regulatory network, hsa-miR-133 regulated ZC3H15, BCLAF1, SRSF11, KTN1, PRPF40A and GNL2. Using the NB4 cell model, hsa-miR-133 treatment inhibited cell proliferation capacity, which could be attenuated by a single mRNA transfection or a combination of ZC3H15 and BCLAF1. At the same time, hsa-miR-133 mimic treatment could significantly accelerated cell apoptosis in NB4 cells, which was also ZC3H15 and BCLAF1 dependent. The concentrations of ZC3H15 and BCLAF1 were investigated in peripheral blood using ELISA method for the clinical control and pAML samples. In pAML samples, the expression levels of ZC3H15 and BCLAF1 were significantly enhanced (P < 0.01), no matter the classification. Conclusion: Collectively, this study hypothesized several promising candidates for pAML formation.